Sustainable water supply in South African rural areas: a comprehensive and contemporary bibliometric analysis - Ishola, Abdulrasaq Ajadi; Gumbo, Trynos; Maramura, Tafadzwa Clementine (Frontiers in Water, 2025)
IntroductionWater is central to the survival of humans, animals, ecosystems, and biodiversity. However, its availability, in the right quantity and quality, has been challenging in most rural areas of developing economies, such as those of South Africa. Particularly in South Africa, this trend has been investigated with much focus on factors militating against sustainable water supply; health, economic, social, and cultural impact of water shortages on rural dwellers, and so on. Each of these studies has suggested one recommendation or the other, yet the water supply problem in the rural areas persists in the country. More concerning is the observation that existing research efforts on the issue have been uncoordinated, with several repeated studies, often in the same area. To better appreciate and contribute to the rural water supply situation in South Africa, this paper conducts a comprehensive bibliometric analysis of contemporary studies on the subject to streamline existing studies into research themes while exposing uncharted research areas for future effort.MethodsAs one of the earliest efforts in this regard, the study adopted the PRISMA protocol to gather literature for the study. A total of 44 published journal articles published between 2022 and 2024 were adopted in this study from the Scopus database. In the analysis of these documents, Biblioshiny and VOSviewer were used to map and analyze scholarly contributions on the topic.ResultsResulting from the analysis, three research areas were found to be saturated with scant effort in the use of digital technologies in rural water management. Existing studies have investigated the health impact of inadequate water supply, the impact of climate change on water availability in the South African rural areas, and the issues confronting water policy implementation in the country.DiscussionMuch research has not been done on the application of information technologies in the management of water in the South African rural areas. Sequel, this study suggests that subsequent research efforts be directed to exploring the application of ICT, IoT, cloud seeding, rain, and fog harvesting in rural water management.